Historical mapping of the urban form and the spatial power distribution in capital Jiankang in East Jin dynasty - Chenwei, Zheng (International Planning History Society Proceedings, 2018)
The Aristocratic Families, which had both political and economic privileges in early Imperial Ages of China with multiple generations working as government officials, had collectively become a core group of East Jin regime. As an important part of the etiquette system under central governance, the capital Jiankang served to display the legitimacy of the regime and to maintain the operational functions of both the nation’s apparatus and the city itself. By using Urban Historical Mapping and Geographic Information System as the methods of the spatial power distribution analysis, this paper focus on the distribution of core capital facilities including worship, administration, military and residence, and also the social status of their users. To conclude, the usage of capital space is a representation of the complex relationship and co-dependence among royalty, aristocratic and plebeians. The area inside the capital city wall is an outstanding space for the privileged class as well as the important representation that the aristocratic class joins the core of national powers. And the aristocrats were spatially distributed spread surrounding outside the capital city rather than congregated in one particular area, which made it easier to form their own power centers, leading to threats to the authority centralization.